2019
DOI: 10.1093/humrep/dez166
|View full text |Cite
|
Sign up to set email alerts
|

CFAP70 mutations lead to male infertility due to severe astheno-teratozoospermia. A case report

Abstract: The use of high-throughput sequencing techniques has allowed the identification of numerous mutations in genes responsible for severe astheno-teratozoospermia due to multiple morphological abnormalities of the sperm flagella (MMAF). However, more than half of the analysed cases remain unresolved suggesting that many yet uncharacterised gene defects account for this phenotype. Based on whole-exome sequencing data from a large cohort of 167 MMAF-affected subjects, we identified two unrelated affected individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…KO males were completely sterile. phological defects and characterized by sperm flagella which are short, coiled, irregular, or even absent-has been associated with a variety of genes in humans and in mice (e.g., AKAP3, AKAP4, AK7, CCDC39, DNAH1, CFAP43, CFAP44, CFAP69, CFAP65, CFAP70, CFAP251, SPATA6, TE KT4, TSSK4, ODF2, ROPN1, FSIP2, TTC21A, and QRICH2) [3,7,[13][14][15][16][17][18][19][20][21][22][23][24][25]27,32,33]. The increasingly large number of such genes emphasizes the extensive genetic heterogeneity of MMAF, strongly suggest that more genes remain to be identified for MMAF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KO males were completely sterile. phological defects and characterized by sperm flagella which are short, coiled, irregular, or even absent-has been associated with a variety of genes in humans and in mice (e.g., AKAP3, AKAP4, AK7, CCDC39, DNAH1, CFAP43, CFAP44, CFAP69, CFAP65, CFAP70, CFAP251, SPATA6, TE KT4, TSSK4, ODF2, ROPN1, FSIP2, TTC21A, and QRICH2) [3,7,[13][14][15][16][17][18][19][20][21][22][23][24][25]27,32,33]. The increasingly large number of such genes emphasizes the extensive genetic heterogeneity of MMAF, strongly suggest that more genes remain to be identified for MMAF.…”
Section: Discussionmentioning
confidence: 99%
“…Recalling that MMAF phenotype are typified by short, coiled, irregular, or absent flagella, previous studies have established that MMAF flagella can be accompanied with ultrastructure abnormalities of axonemes or can lack outer dense fibers or fibrous sheaths [7,11,14,18]. Previous studies have reported that many infertile males harbor genetic polymorphisms for genes encoding cilia and flagella associated proteins (CFAPs), including CFAP43 (also known as WDR96), CFAP44 (also known as WDR52), CFAP69, CFAP70, CFAP251, and CFAP65, thereby associating these genetic loci with MMAF phenotype and disarrangement of 9 peripheral microtubule doublets alongside 2 central microtubules [14,18,21,22,25,27,32]. QRICH2 ablation causes similar phenotype [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exome sequencing allowed us to partially elucidate genetic and physiopathological mechanisms leading to sperm flagellum defects. To date, variants in at least 16 genes have been found to be associated with MMAF phenotype 3–17. We however observe that despite regular new gene identification, about two-thirds of MMAF individuals remain unresolved demonstrating the high genetic heterogeneity of this phenotype 4.…”
Section: Introductionmentioning
confidence: 86%
“…While no direct studies have been done into the role of CFAP52 in Nasonia sperm, CFAP52 shows high expression levels in N. vitripennis testis [ 60 , 61 ]. Splice region changes could affect the functionality of CFAP52, and because of its role in sperm motility, affect male fertility, as was found for splice variants in other cilia- and flagella-associated proteins in humans (CFAP43/44 and CFAP70 [ 62 , 63 ]). Such an effect could directly impact sex allocation in the haplodiploid N. vitripennis, in which fertilization is the key trigger to female development [ 64 ].…”
Section: Discussionmentioning
confidence: 99%